Developments in the Book Layout Design of the Qaraqoyunlu during the Pirbudaq period of the second half of the 9th century AH (857-871 A.H.) - somayeh zarei; Homayun Hajmohammadhoseini (هنرهای زیبا. هنرهای تجسمی)
Qaraquyonlu ruled around the years (810-872 AH). Jahanshah, the most famous king of Qaraqoyunlu, has done his extensive conquests with his son Mirza Abulfath Pirbodagh. His conquests were in areas such as Kerman, Baghdad, Shiraz, Herat, Isfahan, Yazd and Khorasan, but Pirbudaq was the ruler of Shiraz and Baghdad on his father's side. Activities were carried out in the scientific, cultural and intellectual environment of Iran during the period of Jahanshah and Pirbodagh and they had an impact on Iranian culture. To the extent that these emirs were interested in Persian art and literature, they developed and prospered the bookbinding workshops that were left over from the Jalairian and Timurian eras. Meanwhile, in addition to Jahanshah, his crown prince, Pir Bodaq, during his short reign until his death, caused the growth and promotion of book editing, and his period is one of the important periods of the development of book editing, which unfortunately has been less discussed. The present research seeks to answer the following question: what effects did Pirbodaq have on the development of the art of book layout in the second half of the 9th century AH? For this purpose, various aspects of the art of book design, including writing, calligraphy, painting, gilding, and binding, are considered by examining manuscripts in the period of Pirbudaq's rule, with emphasis on the geographical area of his rule in Shiraz and Baghdad. The research method was descriptive-analytical and historical as well. Describing the decorations of the copies and analyzing it by mentioning the name of the scribe, the place of writing and its date, and the historical developments of the time of Pirbudaq and the political situation of that period that caused the transfer of artists. Although Pirbodagh's reign was short and mostly in the two cities of Shiraz and Baghdad, the number and date of the manuscripts written during his time were many in proportion to the short period of his reign, and it shows his support in maintaining workshops, encouraging artists and scribes. In that era, the value of their profession and art has been respected and precious copies were created, which has remained in the history of art under the name of Pirbudaq period. In the end, the result is that Pirbodaq, by creating a context for the exchange of artists, has caused transferring the center of book design from the east to the west of Iran and has boosted the western school of Iran with a variety of artists with different tastes, and in the meanwhile has transferred those artists and has emphasized on the importance of book design workshops. In addition to the importance of book design, Pirbudaq was interested in scribes, poets, painters, and letter writers to provide the necessary materials for writing.